Peter Ackroyd’s London as the backdrop to esoteric corners of the past and present - Bartnik, Ryszard (Adam Mickiewicz University, 2008)
This article concerns Peter Ackroyd’s depiction of London as an arcane labyrinth within which demarcation of the borderline between what is rationally, historically acknowledgeable and what is not is not only highly problematic but in fact undesirable. London, with its echoes of the past, with its people and mysteries, is envisaged as metapolis which exposes, through both its architecture and textual topography, hidden tropes leading to knowledge which spills beyond the knowable. Listening intently to the voices of various rationalists and scientists, as well as occultists and visionaries, the author removes layer after layer of the city’s substance in order to define its spirit and “consolidate its origins” (Ackroyd 2000a: 229). The paradox is that Ackroyd, though a literary historian, defies the use of mechanical rationality placing the occluded knowledge in the foreground so as to allow that cultural and intellectual tradition which sank into oblivion to resurface. It is the past, often complex and mysterious, which foreshadows the present, he seems to be saying, hence his acknowledgement of London’s ignored and forgotten forefathers who, in the eyes of the author, must be rescued from oblivion otherwise the vision of London and Londoners is to remain incomplete.